THE ROLE OF CHRONIC GASTRITIS AMONG PRECANCEROUS DISEASES OF THE STOMACH - Kharchenko, A.V.; Cherno, V.S.; Kharchenko, N.V.; Makarenko, P.M.; Denysovets, I.V.; Денисовець, Т.М.; Myronenko, S.G. (World of Medicine and Biology, 2020)
The purpose of the study is to statistically analyze the condition of the gastric mucosa affected by Helicobacter pylori in young people engaged in sports. Studies of chronic gastritis type B in student volunteers involved in sports. In 92% of cases, chronic gastritis were Helicobacter pylori-associated. Between the degree of contamination of the mucous membrane of Helicobacter pylori and the degree of leukocyte infiltration of the mucous membrane, the Pearson correlation coefficient rxy is 0.935, the correlation is very strong, the determination coefficient is D=rxy2–0.874, the critical value of the correlation coefficient with a probability of 0.95–0.2732, the critical value of the correlation coefficient with a probability of 0.99–0.3511, comparing the correlation coefficient rxy with a critical rcr value for a significance of 0.95–rxy >rcr, comparing the correlation coefficient rxy with a critical rcr value for a significance of 0.99–rxy⸰>rcr to the covariance coefficient is 521.641, this makes it possible to conclude a statistically significant dependence with a probability of 0.99. Thus, chronic atrophic Helicobacter pylori-associated gastritis is a common disease of young people engaged in sports, and is central among precancerous diseases of the stomach.
Keywords: Helicobacter pylori; gastritis; leukocyte infiltration; gastric mucosa